Asymmetric Impact of Infrastructure (Roads, Electrification, Health) on Short-Term Post-Pandemic Regional Growth in South Kalimantan - Utama Ahmed Dima; Muhammad Meidy Nur Hafidz (Ecoplan, 2025)
This research evaluates the relationship between various infrastructure systems and short-term regional growth during the post-pandemic recovery in South Kalimantan, Indonesia. It addresses three deficiencies in Indonesian research: the lack of post-pandemic evidence, the absence of sub-provincial analysis that integrates transport, energy, and social infrastructure, and a focus on quantitative metrics over qualitative and reliability assessments. The two-way fixed effects model that takes into account time-invariant district traits and common year shocks is based on a balanced panel of 13 regencies from 2021 to 2023. The road length, household electrification, the number of primary health facilities, and population are used to figure out real GRDP per capita. The results show that electrification has a positive and statistically significant semi-elasticity. In contrast, the road length exhibits a negative and significant correlation with per capita output, indicating that network quality and connectivity, rather than mere expansion, are crucial for short-term gains. Primary health facilities do not exhibit a statistically significant impact in the short term, which corresponds with the extended timeline of human capital development. Population growth is positive, which is in line with economies of scale. The policy implications back a quality-first agenda: put money into electricity service, move road budgets from expansion to maintenance and completion, and improve primary care while understanding that welfare improvements take time.